Književnost pri pouku latinščine v osnovni šoli - Žmavc, Janja (Keria (Ljubljana), 2004)
The paper explores how classical literature can be practised in the elementary school Latin lessons. The basic presupposition is that literary contents, properly adapted to the personal development of the pupils, should be practised even at elementary school Latin level. Dealing with this topic, the author addersses the question whether, and to what extent, the reception of classical literature is possible in elementary school, and examines the role of the teacher in this respect. The second part of the paper presents a broad definition of literary contents in Latin lessons, what they should contain and what their goals should be. Additionally, it brings some examples of teaching practice in literature lessons.
Keywords: antična književnost; didaktika; jezikovni pouk; književnost; latinščina; osnovne šole